Cognitive Control and Emotional Intelligence: Effect of the Emotional Content of the Task. Brief Reports - Checa, Purificación; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2019)
Emotional intelligence (EI) constitutes a unique form of intelligence and, from performance-based ability models, is conceptualised as the integration of several abilities: use, manage, understand and regulate emotions. The relation between cognitive processes and EI has been less researched, and investigations have not provided consistent results. However, recent studies show that EI, when measured by performance-based ability models but not by other models, plays a relevant role in cognitive processes when emotion is implicated in the tasks. The aim of this study was to examine the execution on hot (emotional) and cool (neutral) cognitive tasks in two groups: one high and one low on EI, in order to determine the role of EI on cognitive processes. The results showed that high and low EI groups did not differ on cool task performance, while the high EI group was better at carrying out the hot task. We discuss these results in relation to recent literature that considers the role of EI in cognitive processes.